1966
DOI: 10.1287/opre.14.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Locations on a Graph with Probabilistic Demands

Abstract: The traffic demands at the stations of a communication network are usually not deterministic. Optimum loca tions found using deterministic techniques are poor when the random nature of the network traffic is con sidered. The concepts of absolute centers and medians are generalized to maximum probability absolute cen ters and medians. Minimum variance points are also considered. Techniques to locate these optimum points are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 5 publications
0
45
0
1
Order By: Relevance
“…(1) and v 2 is a better location than v 3 . In fact, in this particular example, it turns out v 2 is the optimal location.…”
Section: Definitionmentioning
confidence: 98%
See 1 more Smart Citation
“…(1) and v 2 is a better location than v 3 . In fact, in this particular example, it turns out v 2 is the optimal location.…”
Section: Definitionmentioning
confidence: 98%
“…It is also worth noting that FRANK [3,4] has examined another type of stochastic network, one for which the node weights, h i are random variables. Under a different criterion of optimality (involving maximization of the probability that the average travel distance is below a specified value) he has shown that the "locate-facilities-at-nodes" result does not hold in this case.…”
Section: Oriented Network and Extensionsmentioning
confidence: 99%
“…He considered the minimization of the probability of falling below a prespecified threshold. Frank [51,52] considered a model of minimizing the probability that the cost function in the Weber or minimax problems (Love et al [70]) on a network exceeds a given threshold. The threshold concept has been employed in financial circles as a form of insurance on a portfolio, either to protect the portfolio or to protect a firm's minimum profit.…”
Section: The Threshold Objectivementioning
confidence: 99%
“…In these models, the weight of O. Berman et al 243 each nodal point and the length of each link are assumed to be constant and known a priori. Frank (1966) argued that the weight of a nodal point, e.g., the number of messages originating from a node of a communication network, may not be deterministic, but is better represented as a random variable with some probability distribution. This leads to several possible stochastic generalizations of the concepts of medians and centers: in the expected value sense ("absolute expected" median and center), in the sense of maximizing the probability of achieving some threshold ("maximum probability" median and center), or in the sense of variance minimization ("minimum variance" absolute median).…”
mentioning
confidence: 99%
“…This leads to several possible stochastic generalizations of the concepts of medians and centers: in the expected value sense ("absolute expected" median and center), in the sense of maximizing the probability of achieving some threshold ("maximum probability" median and center), or in the sense of variance minimization ("minimum variance" absolute median). These concepts, which were introduced and analyzed in Frank (1966), are discussed in Sect. 11.2 below.…”
mentioning
confidence: 99%